A novel, major, and validated QTL for grain zinc concentration independent of yield traits in tetraploid wheat - Zhaoyong Zeng; Jian Ma; Bingjie Chen; Huaping Tang; Xin Xian; Yuanfeng Huo; Yinggang Xu; Xiaoyan Tang; Xuesong Gao; Guangdeng Chen (The Plant Genome, 2025)
Abstract Zinc deficiency is a critical global health issue, with declining grain zinc concentration (GrZnc) over time. To address this, it is essential to explore and utilize genetic resources from wild relatives to enhance GrZnc in cultivated bread wheat (Triticum aestivum L.). This study aimed to identify quantitative trait loci (QTL) for GrZnc using a recombinant inbred line population (AM population), derived from a cross between the Sichuan‐endemic tetraploid wheat Ailanmai and wild emmer accession LM001. A linkage map was constructed based on the wheat 55K single‐nucleotide polymorphism array, and phenotypic data were collected from five different environments. Four QTL for GrZnc were identified, spanning three chromosomal regions. Notably, a novel and stable QTL, QGrZnc.sau‐AM‐4A, was detected in all environments and the best linear unbiased prediction dataset. This QTL, with LOD values ranging from 2.72 to 9.31, explained 12.31%–30.50% of the phenotypic variance and was mapped to chromosome arm 4AS (54.43–60.02 Mbp). Interestingly, this QTL had no significant effect on key agronomic traits such as spike length, 1000‐kernel weight, kernel number per spikelet, spikelet number per spike, spike density, and plant height, indicating no dilution effects. A kompetitive allele‐specific PCR (KASP) marker, KASP‐AX‐108829087, closely linked to this major QTL, was developed and validated in two different genetic populations. A candidate gene (TRIDC4AG008520) related to zinc absorption and transport was identified within the QGrZnc.sau‐AM‐4A interval. These findings provide insight into the genetic basis of GrZnc and establish a foundation for further fine mapping and map‐based cloning of this locus.